Semantics of Tarbagatai toponyms - Mamysheva , М.Е.; Seitova , Ш.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
The article considers the historical toponyms in the Tarbagatai district of the East Kazakhstan region. The legends of the Tarbagatai region in the Kazakh toponymic folklore are studied, and the meanings, historical and cognitive origins of toponyms are analyzed. The toponyms in the works of travelers of the XVIII-XIX centuries are considered. The settlement names on the territory of the Tarbagatai region have the form of toponymic myths and legendspreserved in the memory of the people. The examples are given from the first paper documents about Altai, Tarbagatai and Zaisan in the Russian researchers’ works of the XVIII century. The information and data in the toponymic legends of Asan kaigy and legends about Tolagay have been collected. The texts about toponymic legends included in the 100-volume collection “Babalar sozi” (Words of the Ancestors). The folk versions of the legend about Tolagay are compared and the origin is explained. The most common legends associated with the place name “Arganaty” among the toponymic legends of Tarbagatai have been systematized. The study of the toponym “Arganaty”is based on M. Kashgari’s dictionary, and the analysis of academician A. Kaidar, scientists A. Abdrakhmanov and T. Zhanuzak.